Military spending and natural resources: evidence from global data - Hassan, Noha Ahmed (AUC Knowledge Fountain, 2014)
Most of the studies show a clear relation between the increase of Oil revenues and the rapid increases in the military expenditure and arms imports (Perlo-Freeman, et al, 2011, Ali 2013). According to the Stockholm International Peace Research Institute (SIPRI, 2010), rising prices and new Oil and Gas exploitation have given governments windfall revenues, some of which have found their way into military spending. Using global data from 1988 to 2013 for 119 countries, this research aim to study: To what extent does the rent from natural resources affect the military spending? Is the countries level of development vis-à-vis military spending? This study will add to the literature available on the consequences of Natural resources on military spending and support the resources curse hypotheses that building up the military-industrial complex intertwined with the natural resources revenues windfall. In addition, it has been shown that natural resources have got negative impact on defense spending such as Oil and natural gas. Moreover, a variable such as Openness has got a crucial significant impact on military spending, while the rent from minerals and coal are ambiguous and has no certain impact on military spending. Keywords: Military Spending; Natural Resources; Openness; Global Data